1995
DOI: 10.1123/ijsn.5.s1.s39
|View full text |Cite
|
Sign up to set email alerts
|

Do Athletes Need More Dietary Protein and Amino Acids?

Abstract: The current recommended daily allowance (RDA) for protein is based primarily on data derived from subjects whose lifestyles were essentially sedentary. More recent well-designed studies that have employed either the classic nitrogen balance approach or the more technically difficult metabolic tracer technique indicate that overall protein needs (as well as needs for some specific individual amino acids) are probably increased for those who exercise regularly. Although the roles of the additionally required die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 53 publications
(59 reference statements)
1
23
1
2
Order By: Relevance
“…Additional protein needs have been suggested for several types of strength and endurance exercise (7,26,27). In the present study, significant gains in net protein accretion were detected for the treatment receiving protein, even with what would amount to a moderate increase in protein intake (0.13 g·kg Ϫ1 ).…”
Section: Post-exercise Intake Alters Protein Homeostatiscontrasting
confidence: 39%
See 1 more Smart Citation
“…Additional protein needs have been suggested for several types of strength and endurance exercise (7,26,27). In the present study, significant gains in net protein accretion were detected for the treatment receiving protein, even with what would amount to a moderate increase in protein intake (0.13 g·kg Ϫ1 ).…”
Section: Post-exercise Intake Alters Protein Homeostatiscontrasting
confidence: 39%
“…Previously, Lemon (26) suggested that athletes have greater protein requirements than sedentary individuals and proposed that the current RDA of 0.8 g·kg Ϫ1 ·d Ϫ1 be increased to between 1.4 and 1.8 in strength athletes and to between 1.2 and 1.4 in endurance athletes (26). Additional protein needs have been suggested for several types of strength and endurance exercise (7,26,27).…”
Section: Post-exercise Intake Alters Protein Homeostatismentioning
confidence: 97%
“…The protein breakdown, resulting in BCAA degradation, increases during intense exercise with a subsequent alanine release increment (Consoli et al, 1990;Lemon, 1995;MacLean et al, 1996), in fact transamination of pyruvate forms alanine transferring the α-amino group and this reaction involves glutamate and α-ketoglutarate. In agreement with our previous observations (De Palo et al, 1993, 1996) MacLean et al (1996 demonstrated a significantly greater amount of alanine during exercise in a BCAA trial than in a control trial.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that athletes need a high-protein diet is intuitively attractive, and indeed there is evidence that the requirement for protein is increased by physical activity (Lemon, 1995). Muscles consist largely of protein and their involvement is fundamental to performance in all sports.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%